2012
DOI: 10.4304/tpls.2.4.657-663
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Listening and Other Language Skills in International English Language Testing System

Abstract: Listening comprehension is the primary channel of learning a language. Yet of the four dominant macro-skills (listening, speaking, reading and writing), it is often difficult and inaccessible for second and foreign language learners due to its implicit process. The secondary skill, speaking, proceeds listening cognitively. Aural/oral skills precede the graphic skills, such as reading and writing, as they form the circle of language learning process. However, despite the significant relationship with other lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 17 publications
6
47
3
2
Order By: Relevance
“…The findings of her study showed that one way to improve speaking skill is to interact with others, learn from others, and the choice of the topics based on the learners' interests in order to encourage them. Bozorgian (2012) investigated the relationship between listening skill and the other language skills. The results revealed that there is a close correlation between listening comprehension and language proficiency.…”
Section: Previous Studies On the Factors Affecting Speaking Skillmentioning
confidence: 99%
“…The findings of her study showed that one way to improve speaking skill is to interact with others, learn from others, and the choice of the topics based on the learners' interests in order to encourage them. Bozorgian (2012) investigated the relationship between listening skill and the other language skills. The results revealed that there is a close correlation between listening comprehension and language proficiency.…”
Section: Previous Studies On the Factors Affecting Speaking Skillmentioning
confidence: 99%
“…Without adequate listening skills, sustaining learning processes that might be boring in first or foreign language education, does not seem possible [9]. Within the process of language acquisition the necessity for effective listening skills obliges us to reveal whether the students know how to listen or not [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested by many researchers like Bozorgian (2012) and Feyten (1991) and Richard (2008) that enhancing the speaking skill is strongly related to the students' progress in the listening skill. Celik and Yavuz (2015) say that understanding the nature of the language skills and how related they are a precondition for any successful learning / teaching process.…”
Section: Theoretical Framementioning
confidence: 99%
“…She also adds that only through listening to authentic materials by native speakers can learners produce correct pronunciation and learn how to improve their use of features like stress and intonation. A point supported by Bozorgian (2012) and Abbas (2013) who believe that listening is the basic and most essential skill in any English language process and that it has to be treated with more care and given more time.…”
Section: Theoretical Framementioning
confidence: 99%
See 1 more Smart Citation